Let It Grow: The Role of Growth Factors in Managing Chemotherapy-Induced Cytopenia - Ruah Alyamany; Ahmed Alnughmush; Hazzaa Alzahrani; Mansour Alfayez (Current Oncology)
Chemotherapy-induced cytopenia (CIC) is characterized by neutropenia, anemia, and thrombocytopenia, which are common and serious complications in cancer treatment. These conditions affect approximately 60% of patients undergoing chemotherapy and can significantly impact quality of life, treatment continuity, and overall survival. The use of growth factors, including granulocyte colony-stimulating factors (GCSFs), erythropoietin-stimulating agents (ESAs), and thrombopoietin receptor agonists (TPO-RAs), has emerged as a promising strategy for managing CIC. However, the use of these growth factors must be approached with caution. This review provides an overview of the mechanisms, efficacy, and safety of growth factors in the management of CIC. Additionally, we discuss predictive markers for treatment response, potential risks, and highlight areas for future research.